: SISTEM INFORMASI PELAYANAN PUBLIK KOTA MALANG - Dwi Haris Sanjaya; Yoga Firmansyah; Ahmad Sirojun Nuha; Hilmi Tsaqif (Department of Science and Technology Ibrahimy University, 2020)
E-government is expected to help the achievement of the government, such as improving administration, internal efficiency, providing public services and increasing opportunities for citizens to participate in democratic institutions and processes. In the National IT Framework study by BAPPENAS, one of the pillars that need to be formed is the Electronic Government (E-Government) for Good Governance to accelerate the good, efficient, and effective form of governance. In the process of implementing E-Government, Indonesia still faces obstacles. Malang City with the increasing of peoples it is necessary for the government to improve the performance of its government. One of the ways is by establishing a Public Service information system. Therefore, in this case, we created the Malang City Public Service Information System Based on the WEB. The development of this system is implemented by pair programming ie. observing the collaboration of each team element. The results of this development is WEB-based Malang City Public Service Information System which consists of several public services. The system is managed online and dynamically. With this system, it is expected to be able to help the process of public services in Malang.